Leadership Ethics in the Formulation of Corporate Strategy with Special Reference to Ethical Systems of Imam Al-Ghazali - Ridzuan Masri (Universiti Sains Islam Malaysia, 2024)
Strategy formulation within the framework of corporate strategic management is a process to plan for long term organizational sustainability. To plan a strategy, an organization needs all the resources available and utilizes these resources to achieve its vision, mission and strategic objectives set out in the beginning. how eve^ the use and utilization o f resources without control will only lead to strategies designed to be a source of damages to the organization that eventually also involves stakeholders directly or otherwise. Thus, from the facets of strategic management, each level in the organizational leadership must have a value of embedded ethics as guidance in the decision making process. This paper will be referring extensively the work of Abu Hamed Mohammad ibn Mohammad al- Ghazali, particularly Ihya ' 'Ulumuddin within the scope of formulation stage of corporate strategy in the aspect of the formation of the vision and mission of the organization. In the framework of Imam al-Ghazali ethics, critiques of the modern theory of motivation that moving psychological stimulus of employees from the modern perspective will also be explicated. Due to the Islamic worldview which recognizes that knowledge is all belongs to God, therefore, not all theoretical framework o f the modern management science be relinquished if it noticeably leads to goodness from the perspective of the ummah development. Predicating from this worldview, al-Ghazali's framework of ethics can be an alternative guideline for strategic decision-making process to take place within the modern framework o f modern strategic management theory.